Characteristics of patients with coexisting IgA nephropathy and membranous nephropathy. (15th October 2018) - Chen, Pei; Shi, Su-Fang; Qu, Zhen; Zhao, Na; Xie, Xin-Fang; Lv, Ji-Cheng; Liu, Li-Jun; Zhang, Hong
Abstract: Background: Coexistence of IgA nephropathy (IgAN) and membranous nephropathy (MN) in the same patient is rare. Few studies have reported the clinical and pathological features of patients with combined IgAN and MN (IgAN–MN). Methods: The clinico-pathological features, levels of galactose-deficient IgA1 (Gd-IgA1) and autoantibodies against M-type transmembrane phospholipase A2 receptor (anti-PLA2 R) in sera were compared among IgAN–MN, IgAN, and MN patients. Results: Twenty-six patients with biopsy-proven IgAN–MN were enrolled. The mean age at biopsy was 43.6 ± 15.9 years, and 65.4% were male. Proteinuria and estimated glomerular filtration rate (eGFR) levels in patients with IgAN–MN were similar to that of MN patients. Compared with the IgAN patients, IgAN–MN patients showed a higher median proteinuria level (4.3 vs. 1.2 g/day, p  < .001), and a higher mean eGFR level (101.8 ± 25.4 vs. 78.6 ± 26.9 mL/min/1.73 m 2, p  < .001). IgAN–MN patients presented with milder pathological lesions than IgAN patients according to the Oxford Classification. IgAN–MN patients had comparable serum levels of Gd-IgA1 with those of IgAN patients (353.4 ± 95.5 vs. 347.0 ± 109.6 U/mL, p  = .801). Percentage of IgAN–MN patients with detectable serum levels of anti-PLA2 R was lower than that of MN patients (38.5% vs. 68.6%, p  = .011). Conclusions: IgAN–MN patients display similar clinical features to MN patients and milder pathological lesions than IgAN patients. IgAN–MN patients have similar levels of Gd-IgA1 to those of IgAN patients, and a lower proportion of anti-PLA2 R than MN patients.